The effectiveness of Instagram ads as a promotional platform in selling product at Sthala Ubud Bali using the EPIC model method - I Komang Ari Sadewa; I Gusti Agung Bagus Mataram; I Gusti Agung Mas Krisna Komala Sari (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2023)
Current technological developments affect global marketing trends. This development has made marketers change their marketing strategies to internet marketing, one of which is Sthala, a Tribute Portfolio Hotel, Ubud Bali by Marriott International which wants the products marketed to cover the global market, the objective in this study is of course to measure the role of Instagram in carrying out promotions and sales so that the level of effectiveness of the advertisements that are run must be measured. The researcher was interested to analyse the effectiveness of hotel advertisements through the Instagram platform in selling products Using variables from EPIC (empathy, persuasion, impact, and communication) the level of advertising effectiveness can be determined. The sampling technique used for this study was purposive sampling, consisting of Instagram followers of this hotels, with total 100 respondents were collected as samples. This study uses the EPIC model as a method for calculating effectiveness which consists of four dimensions, namely empathy, persuasion, impact, and communication. The results of research and examination of Sthala, a Tribute Portfolio Hotel, Ubud Bali by Marriott Internasional’s Instagram is considered very effective for the empathy dimension, the persua-sion dimension, the impact dimension, and the communication dimension. Overall, these findings conclude that advertising Sthala, a Tribute Portfolio Hotel, Ubud Bali by Marriott International via Instagram is very effective. The effectiveness of hotel room sales growth was also tested which shows positive growth results but due to Covid-19, sales growth has decreased. This is indicated by data on room sales from 2018 to 2019 it rose significantly and in 2020 it dropped dramatically and experienced another increase in 2021 to 2022.